On Horseback Through Asia Minor - Burnaby, Frederick (Oxford, New York Oxford University Press, 1996)
In the winter of 1876, Captain Frederick Burnaby rode 1,000 miles eastwards from Constantinople to see for himself what the Russians were up to in this remote corner of the Great Game battelfield. With his servant Radford, he spent 5 months riding across some of the cruellest winter landscape in the world before hastening home to write this work.
Include Index
Keywords: Travel -- Turkey -- Burnaby, Fred, 1842-1885